Message from the Editor-in-Chief of International Journal of Science Annals, 2024 - Yu. B. Melnyk (International Journal of Science Annals)
Background and Aim of Study: The publication of scientific papers in the media is becoming more and more accessible. This creates competition between scientific journals. It can ensure an increase in the scientific level of published products. The aim of the study: to familiarise both the readers and the authors with the activities of the International Journal of Science Annals (IJSA). Results: The results of the journal’s activities over the past year and its future prospects were analysed. Authors were informed about the benefits of publishing in the IJSA and about the possibility of participating in international scientific events (conferences, competitions) organised with the participation of the journal. Conclusions: The high competition in the publishing market requires the IJSA to systematically improve the scientific level of the journal, to adhere to high publishing standards and ethical norms, to create coordinated, productive relationships between authors and reviewers, and to provide them with new opportunities.